2008
DOI: 10.1111/j.1365-2826.2008.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Iron Transport Across the Placenta: Regulation and Interactions

Abstract: Iron and copper are both essential micronutrients and are required for a wide variety of enzymatic and other processes within the developing foetus. Transfer of both nutrients across the placenta is tightly regulated. In this review, we consider their mechanisms of transport, how the transfer is modulated in response to nutritional requirements and how the two metals interact. Iron uptake is via the transferrin receptor, followed by endocytosis, acidification of the vesicle, and release of the iron into the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 47 publications
(64 reference statements)
2
56
0
9
Order By: Relevance
“…7B; ϩCu). These observations reveal a necessary role for Atp7a for intestinal copper acquisition during late stage pregnancy when maternal copper transfer across the placenta peaks in mammals (20). Consistent with this role was the finding that fetuses harvested from pregnant Atp7a int/int females just prior to parturition (E19) contained less than 20% of the copper content of the same-aged fetuses derived from wild-type females (Fig.…”
Section: Atp7asupporting
confidence: 60%
See 1 more Smart Citation
“…7B; ϩCu). These observations reveal a necessary role for Atp7a for intestinal copper acquisition during late stage pregnancy when maternal copper transfer across the placenta peaks in mammals (20). Consistent with this role was the finding that fetuses harvested from pregnant Atp7a int/int females just prior to parturition (E19) contained less than 20% of the copper content of the same-aged fetuses derived from wild-type females (Fig.…”
Section: Atp7asupporting
confidence: 60%
“…Moreover, the finding that late-term fetuses from affected mothers were severely copper deficient, despite a normal size and morphology, provided further evidence that late gestational development rather than embryogenesis was sensitive to the loss of Atp7a in the maternal enterocyte. Since the most active transfer of copper across the placenta to the fetus occurs during the last trimester of pregnancy in mammals (20,21), these observations suggest that maternal expression of Atp7a in the enterocyte is necessary to meet this demand, a conclusion that was also supported by the finding that copper supplementation of Atp7a int/int fe- males at day E17 of pregnancy could prevent sudden perinatal death of the offspring.…”
Section: Discussionmentioning
confidence: 80%
“…Of particular interest is the placenta, which has been shown to express ZIP14 (17). Placental iron transport involves endocytosis of TF from the maternal circulation and dissociation of iron from TF prior to export into the fetal circulation (43). The transport of iron out of the endosome in syncytiotrophoblast cells of the placenta was thought to be mediated by DMT1 (44), until the generation of DMT1 knockout mice demonstrated that it was not required (6).…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, animal studies revealed that hepcidin and iron levels in the fetal liver may also regulate maternal-fetal iron transport. [14][15][16] We aimed to study maternal and fetal hepcidin and other iron parameters to improve our understanding of human placental iron transport. Therefore, we retrospectively assessed plasma concentrations of these indices in primigravidae, as a function of placental P. falciparum infection and maternal anemia, and in corresponding cord-blood samples.…”
Section: Introductionmentioning
confidence: 99%